Morphological changes and two Nodal paralogs drive left-right asymmetry in the squamate veiled chameleon (C. calyptratus) - Shylo, Natalia A.; Smith, Sarah E.; Price, Andrew J.; Guo, Fengli; McClain, Melainia; Trainor, Paul A. (Frontiers in Cell and Developmental Biology, 2023)
The ancestral mode of left-right (L-R) patterning involves cilia in the L-R organizer. However, the mechanisms regulating L-R patterning in non-avian reptiles remains an enigma, since most squamate embryos are undergoing organogenesis at oviposition. In contrast, veiled chameleon (Chamaeleo calyptratus) embryos are pre-gastrula at oviposition, making them an excellent organism for studying L-R patterning evolution. Here we show that veiled chameleon embryos lack motile cilia in their L-R organizer, consistent with the loss of motile cilia being a synapomorphy of all reptiles. Furthermore, in contrast to avians, geckos and turtles, which have one Nodal gene, veiled chameleon exhibit expression of two paralogs of Nodal in the left lateral plate mesoderm, albeit in non-identical patterns. Using live imaging, we observed asymmetric morphological changes that precede, and likely trigger, asymmetric expression of the Nodal cascade. Thus, veiled chameleons are a new and unique model for studying the evolution of L-R patterning.